Maintaining cutomer relationships on Facebook - Trakimavičiūtė, Giedrė (Information & Media, 2017)
This paper shows how Lithuanian retail companies maintain customer relationships on Facebook. Most of the customers read reviews to help themselves decide where to buy all sorts of items. That being said, it is crucial to the modern company to use social media for communication with customers and especially to answer all complains. To aim of this paper was to answer the following questions: which of retail company follows all the suggestions to maintain good relationships with their customers? And which one uses the best techniques to do that? A qualitative analysis of the content of Facebook posts by retail companies was made in a period of a year. It was noticed that MAXIMA and NORFA had the best strategy in interacting with their customers on Facebook, but when the new market share (LIDL) was introduced to the market, it suggested a new way of communication and showed that even a lot of communication can be good if you react to most of your customers questions and complains.
Keywords: ...